The Problematic of Digital Inequality in an Educational Political Policy Perspective - Rd. Heri Solehudin (LP. Ma'arif Janggan Magetan, 2024)
This research explores and analyzes the problem of digital inequality in education, especially from the perspective of educational political policy. Digital inequality, which includes disparities in access and use of technology among students, can be a serious obstacle to achieving the goal of equitable and inclusive education. This research uses a policy analysis approach to investigate educational political policies that may be the cause or solver of digital inequality by involving case studies that occurred at Muhammadiyah Middle School in Depok City,By analyzing the role of educational political policies in digital inequality, this research aims to present findings that can contribute to the formulation of more effective policies in overcoming this inequality. It is hoped that the results of this research will provide insight for policy makers to develop policy strategies that can minimize digital inequality among students, as well as improve the overall quality and accessibility of education.